2020
DOI: 10.1146/annurev-ecolsys-011720-121505
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Interactions and Macroevolution: A New Field with Old Roots

Abstract: Linking interspecific interactions (e.g., mutualism, competition, predation, parasitism) to macroevolution (evolutionary change on deep timescales) is a key goal in biology. The role of species interactions in shaping macroevolutionary trajectories has been studied for centuries and remains a cutting-edge topic of current research. However, despite its deep historical roots, classic and current approaches to this topic are highly diverse. Here, we combine historical and contemporary perspectives on the study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 164 publications
(294 reference statements)
3
64
0
Order By: Relevance
“…17). Opening up new niches, which can also expand due to diversification increases of the host-plant families through time [64][65][66] , would allow a continuous increase in diversification rates through time in a dynamic biotic environment, lending support to the primary role of ecological interactions in clade diversification over long timescales-a longcontentious issue 29 . Nonetheless, when taking into account the possibility that rates may have been heterogeneous across the phylogeny, we find that the diversification of three lineages (those feeding on Annonaceae, Lauraceae and Papaveraceae) had early rates of speciation that are higher than the ancestral rates, but slowed down through time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17). Opening up new niches, which can also expand due to diversification increases of the host-plant families through time [64][65][66] , would allow a continuous increase in diversification rates through time in a dynamic biotic environment, lending support to the primary role of ecological interactions in clade diversification over long timescales-a longcontentious issue 29 . Nonetheless, when taking into account the possibility that rates may have been heterogeneous across the phylogeny, we find that the diversification of three lineages (those feeding on Annonaceae, Lauraceae and Papaveraceae) had early rates of speciation that are higher than the ancestral rates, but slowed down through time.…”
Section: Resultsmentioning
confidence: 99%
“…However, a major knowledge gap lies in our understanding of the evolutionary links and drivers of host-plant shifts, genome-wide signatures of adaptations and processes of species diversification 28 . As noted by Hembry and Weber 29 , this implies that the questions of if, when and how coevolution has an impact on macroevolutionary dynamics remain open challenges. Here we address this gap with an emblematic group that was instrumental in Ehrlich and Raven's model-the swallowtail butterflies (Lepidoptera: Papilionidae).…”
mentioning
confidence: 99%
“…Our results suggest that there are general patterns across plants and animals, despite considerable uncertainty in the literature about how species interactions might impact diversification (e.g. Jablonski, 2008; Ricklefs, 2010; Weber et al ., 2017; Chomicki et al ., 2019; Hembry and Weber, 2020). Below we discuss the potential causes of these patterns, and their broader implications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reviewed the general topic of species interactions and macroevolution (e.g. Weber et al ., 2017; Hembry and Weber, 2020), but little consensus has emerged about the effect of different interaction types on diversification. For example, Jablonski (2008) reviewed paleontological and neontological studies, and showed that negative interactions at the organismal level (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Disentangling these opposing effects is challenging because previous macroecological studies have generally been restricted to either relatively few traits or limited samples of species. In addition, previous studies have been impeded by the lack of suitable methods for detecting the impact of species interactions on trait evolution [40][41][42], although recent progress has been made in developing such methods for use in standard comparative analyses [20,22,24,43,44]. By incorporating species interactions directly into phylogenetic models of trait evolution, these developments overcome some of the issues faced by phylogenetic and trait approaches for studying community assembly that rely on overly simplistic comparisons to randomly assembled communities [43,45,46].…”
Section: Introductionmentioning
confidence: 99%